Mothers' knowledge of the causes and prevention associated with diarrhea among under-five children in Hlaing Thar Yar Township, Yangon, Myanmar - Lwin, Khaing Zar; Edi Putra, I Gusti Ngurah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Diarrhea among under-five children remains a major public health problem in developing countries, such as Myanmar. Its complications contribute to the worse health outcomes as well as increase the child mortality in Myanmar. Hlaing Thar Yar was recognized as a township with the highest incidence of diarrhea in Yangon region. Aims: This study aimed to identify the association of mother’s knowledge on diarrhea with the diarrheal disease among under-five children in Hlaing Thar Yar Township, Yangon, Myanmar. Methods: This was a cross-sectional study by collecting primary data in the Hlaing Thar Yar Township of Yangon, Myanmar from November to December 2016. About 277 records of mothers and their under-five children have been collected through multistage random sampling. A dependent variable in this study was the occurrence of diarrhea among under-five children whilst independent variables consisted of socio-demographic characteristics of parents and five domains of mother’s knowledge on diarrhea. Data were analyzed by using univariate, bivariate and multivariate analysis. Results: This study found that a half (53.43%) of under-five children suffered diarrhea within two weeks prior to the survey. Based on multivariate analysis by controlling all socio-demographic factors, two out of five domains of mother’s knowledge showed significant association. An increased one score of mother’s knowledge on causes and prevention of diarrhea contributed to decrease the likelihood of diarrheal disease by 37% (OR=0.63; 95%CI=0.44-0.90) and 27% (OR=0.73; 95%CI=0.54-0.99), respectively. Conclusions: This study confirmed that the knowledge of mothers on causes and prevention of diarrhea appears to have important effects on the occurrence of diarrhea among the under-five children. Therefore, health promotion program with an emphasis on providing information related to diarrhea causes and prevention is worth to enhance mother’s knowledge and their ability to prevent diarrhea among under-five children in Hlaing Thar Yar Township, Yangon.